2021
DOI: 10.1371/journal.pone.0255055
|View full text |Cite
|
Sign up to set email alerts
|

Searching in the dark: Shining a light on some predictors of non-response to psychotherapy for borderline personality disorder

Abstract: Background Borderline Personality Disorder (BPD) is a prevalent and serious mental health condition. People can experience recovery or remission after receiving psychotherapy for BPD; however, it is estimated that about 45% of people in well conducted treatment trials do not respond adequately to current psychological treatments. Aim To further advance psychotherapies for BPD by identifying the factors that contribute to the problem of non-response. Method 184 consecutive participants with BPD in community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 114 publications
(169 reference statements)
0
10
0
1
Order By: Relevance
“…Internal consistency of this approach was excellent ( α = 0.90). Validity was demonstrated in previous studies of process–outcome (Hashworth et al, 2021 ; Huxley et al, 2019 ; Miller et al, 2018 ; Woodbridge, Reis, et al, 2021 ). The McLean Screening Instrument (MSI) (Zanarini et al, 2003 ) cut‐off of 7 was used to group participants as described below.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Internal consistency of this approach was excellent ( α = 0.90). Validity was demonstrated in previous studies of process–outcome (Hashworth et al, 2021 ; Huxley et al, 2019 ; Miller et al, 2018 ; Woodbridge, Reis, et al, 2021 ). The McLean Screening Instrument (MSI) (Zanarini et al, 2003 ) cut‐off of 7 was used to group participants as described below.…”
Section: Methodsmentioning
confidence: 77%
“…Increasingly, dominant diagnostic and classification systems are moving towards classification of personality within a spectrum of severity (e.g., personality functioning, American Psychiatric Association, 2013 ; personality organisation, Lingiardi & McWilliams, 2017 ; and personality severity, World Health Organization, 2019 ). While there currently exists a number of effective and evidence‐based treatments for personality disorder (Bateman et al, 2015 ), a subgroup of patients remain unwell despite therapeutic intervention (Woodbridge, Reis, et al, 2021 ; Woodbridge, Townsend, et al, 2021 ). As reflected by the ‘functioning poorly’ group, our results highlight a group of severely unwell patients with unique challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with borderline personality disorder, it has been shown that those having a preoccupied attachment style were more likely to not respond to intervention. It has been argued that preoccupied attachment style might complicate the engagement in the therapeutic treatment and the alliance with the therapist [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also argued that preoccupied attachment style might complicate the engagement in the therapeutic treatment and the alliance with the therapist ( 35 ).…”
Section: Discussionmentioning
confidence: 99%